PTH-073 Social Media use by Inflammatory Bowel Disease and Viral Hepatitis Patients and Potential Application for Healthcare. (4th June 2013) - Timms, C; Chan, D; Kang, J-Y; Forton, D; Poullis, A
Abstract : Introduction: Currently, inflammatory bowel disease (IBD) and viral hepatitis management involve regular visits to hospital clinics. This requires frequent time taken out of work and family life to attend. This study investigates patients' current social media use and attitude toward the potential role social media could have in reducing their hospital visits. Methods: Over a one month period (November 2012), IBD and hepatitis B and C patients attending the Gastroenterology and Hepatology Outpatient Departments of St. George's Hospital were identified. Convenience sampling was used; all IBD and hepatitis B and C patients encountered in these clinics were asked to participate. Patients were asked to complete a questionnaire, gathering information about their disease, current use of social media and their views about social media in the management of their disease Results: 180 patients participated in the study: 95 patients were male and 85 were female. The combined mean age was 38.9 years (range of 15–85 years). 112 patients had IBD and 68 had viral hepatitis. The mean age for the IBD patients was 39 years (range 16–85 years) and the mean age for the hepatitis patients was 38.6 years (range 15–63 years). 46 (43.75%) of the IBD patients and 49 (72%) of the hepatitis patients were male. In our study, 82.1% of the IBD and 72.1% of the viral hepatitis patients used one or more social networking site. Facebook was the most popular site. 29.5% of the IBD and 33.8% of the viral hepatitis patients used social media for support with their illness. 80.4% of the IBD patients and 72.9% of the viral hepatitis patients said they would be happy with some form of social media interaction by healthcare professionals. 84.8% of the IBD patients and 72.1% of the viral hepatitis patients were in favour of a specific social media website for their disease. Conclusion: A large proportion of patients with IBD and viral hepatitis already use social networking sites. This study suggests that the majority of both IBD and viral hepatitis patients would welcome the use of social media as part of their illness management. There are already some social media sites that have been setup for these patient groups. Increasing the awareness of these sites and further research investigating the integration of social media into the current management of both these patient groups is needed. Disclosure of Interest: None Declared.